2018
DOI: 10.1073/pnas.1722056115
|View full text |Cite|
|
Sign up to set email alerts
|

CD52 glycan binds the proinflammatory B box of HMGB1 to engage the Siglec-10 receptor and suppress human T cell function

Abstract: SignificanceInflammation is a protective response of the body’s immune system against harmful stimuli such as pathogenic microorganisms, toxins, or damaged cells. However, if excessive or prolonged, inflammation may be harmful and therefore has to be regulated. Soluble CD52 is a natural sialoglycopeptide and immune regulator that suppresses inflammatory responses. We elucidated the mechanism of this effect by showing that soluble CD52 first sequesters a mediator of inflammation called HMGB1; in turn, this prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 26 publications
3
64
0
Order By: Relevance
“…Studies have shown that Siglec-10 plays an important role in regulating the immune balance of in ammatory diseases. For example, the interaction of Siglec-10 and CD24 reduces the in ammatory response associated with the damage-associated molecular patterns (DAMPs) by inhibiting the activation of high mobility group box 1 (HMGB1) and NF-κB [15][16][17][18]. The interaction between Siglec-10 expressed on human DC and pseudaminic acid can increase the expression of IL-10 through MyD88 and p38 MAPK signaling pathway to promote anti-in ammatory function [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that Siglec-10 plays an important role in regulating the immune balance of in ammatory diseases. For example, the interaction of Siglec-10 and CD24 reduces the in ammatory response associated with the damage-associated molecular patterns (DAMPs) by inhibiting the activation of high mobility group box 1 (HMGB1) and NF-κB [15][16][17][18]. The interaction between Siglec-10 expressed on human DC and pseudaminic acid can increase the expression of IL-10 through MyD88 and p38 MAPK signaling pathway to promote anti-in ammatory function [19].…”
Section: Introductionmentioning
confidence: 99%
“…Since the in ammatory response is an important progress in aSAH, in which excessive reaction usually causes serious harm [18], Siglec-10, an anti-in ammatory factor, may affect the recovery of aSAH patients by adjusting the balance of pro-in ammatory and anti-in ammatory. This has not been proved in vivo or in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…CD52 is an important immune regulator on T-cell activation as previous reports, which can modulate T-cell activation either by its intracellular signal pathways or by the interaction of soluble CD52 and Siglec-10 expressing on T cells (30,31). Functional enrichment analysis of 933 differential expression genes in CD52 high and CD52 low found that DEGs were significantly enriched in terms of T cell activation, which is consistent with previous reports.…”
Section: Discussionmentioning
confidence: 70%
“…CD52 is an important immune regulator on T-cell activation as previous reports, which can modulate T-cell activation either by its intracellular signal pathways or by the interaction of soluble CD52 and Siglec-10 expressing on T cells (31,32). Functional enrichment analysis of differential expression genes in CD52 high and CD52 low found that DEGs were significantly enriched in terms of T cell activation, which is consistent with previous reports.…”
Section: Discussionmentioning
confidence: 70%